The Effects of Ultrasound on the Rehydration of Konjac Glucomannan/Soy Protein Isolate Gel and Simulation of Gas-Liquid Interface Evolution During the Rehydration Process - Jiqiang Yan; Shizhong Jiang; Qin Wang; OuJun Dai; Zhuoer Yang; Biyao Huang; Ruoyu Huang; Zhenghao Chi; Yilan Sun; Jie Pang (Foods)
Soy protein isolate (SPI) possesses potential gelling properties, making it suitable for gel-based applications. However, the gel network stability and mechanical properties of SPI are relatively poor and can be improved through modifications or by combining it with other polymers, such as Konjac Glucomannan (KGM). Combining SPI with KGM can overcome the poor gel network stability and mechanical properties of SPI, but it reduces the water-absorbing capacity of the gel network after drying, which affects the quality characteristics of plant-based protein rehydrated foods and limits the economic feasibility of soy protein foods. In this study, SPI and KGM are the main research objects. By using the alkali method to construct SPI/KGM dry gels with good gel properties, the influence of different ultrasonic powers on the rehydration kinetics and performance changes of SPI/KGM dry gels is examined. The speed and state of water entering the pores are simulated by constructing different pore-size capillary filling models, and the rehydration mechanism of the gel is elucidated. This study provides research ideas and a theoretical basis for the application of ultrasonic wave technology in the study of dry product rehydration performance.